The anthropology of moralities - Heintz, Monica (Berghahn Books, Inc., 2009)
Anthropologists have been keenly aware of the tension between cultural relativism and absolute norms, and nowhere has this been more acute than with regards to moral values. Can we study the Other's morality without applying our own normative judgments? How do social anthropologists keep both the distance required by science and the empathy required for the analysis of lived experiences? The plurality of moralities has not received an explicit and focused attention until recently, when accelerated globalization often resulted in the collision of different value systems. Observing, describing a.